2012
DOI: 10.1159/000336377
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet Programs for Metabolic Disturbances in Offspring despite Leptin Sensitivity

Abstract: A fatty diet during pregnancy in mouse dams causes metabolic abnormalities (similar to metabolic syndrome in humans) in the rodents’ offspring. We tested the hypothesis that the offspring of dams fed a high-fat diet during pregnancy and lactation develop metabolic abnormalities and leptin resistance. Pregnant C57BL/6 mice (n = 20) were fed either standard chow (SC; 19% fat) or a high-fat diet (HF; 49% fat). After weaning, male offspring were divided into four groups, according to the diet of dams and offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 91 publications
7
33
0
3
Order By: Relevance
“…These results indicated that maternal HLE diet during gestation itself might program the development without obesity. Other researchers also observed the absence of obesity during gestation in rodents fed with HLE diet ( 30 ). Because chronic high-fat diet consumption may result in a greater lipid transfer to the fetus regardless of maternal obesity ( 9 ), the total lipid content in neonate and weaning mouse livers was signifi cantly increased in the HLE diet group in our study.…”
Section: Discussionsupporting
confidence: 73%
“…These results indicated that maternal HLE diet during gestation itself might program the development without obesity. Other researchers also observed the absence of obesity during gestation in rodents fed with HLE diet ( 30 ). Because chronic high-fat diet consumption may result in a greater lipid transfer to the fetus regardless of maternal obesity ( 9 ), the total lipid content in neonate and weaning mouse livers was signifi cantly increased in the HLE diet group in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Offspring exposed to a maternal HFD in utero and/or postnatally developed manifestations of the Metabolic Syndrome, such as insulin resistance, increased liver mass and triglyceride content, hepatic steatosis, increased visceral fat mass and adipocyte hypertrophy but not central leptin resistance [30, 41]. These changes are accompanied by increased serum concentrations of tumor necrosis factor α (TNFα) and interleukin 1β (IL-1β) [30].…”
Section: Mousementioning
confidence: 99%
“…Similar changes are observed even when the offspring are weaned to a non-HFD. Interestingly, exposure to HFD in utero has a more detrimental effect on the liver of the offspring than does HFD after weaning [41]. Moderate steatosis and NASH has been shown to be associated with increased expression of genes of lipogenesis, oxidative stress and inflammation, in addition to alterations in activity of enzymes of the electron transport chain [37, 47].…”
Section: Mousementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a healthy offspring diet, a post-weaning Western-type offspring diet exacerbated the effects of the mother’s obesity on weight gain or adiposity (Bayol et al, 2007; Chen et al, 2009; Ong and Muhlhausler, 2014; White et al, 2009), glucose/insulin regulation (Arentson-Lantz et al, 2014; Benkalfat et al, 2011; Chen et al, 2009; Flynn et al, 2013; Khanal et al, 2014; Li et al, 2013; Page et al, 2009; Rajia et al, 2010; Shalev et al, 2010; Srinivasan et al, 2006; Volpato et al, 2012), cardiovascular measures (Elahi et al, 2009; Fan et al, 2013; Turdi et al, 2013), or fatty liver (Bouanane et al, 2010; Bruce et al, 2009; Hellgren et al, 2014; Li et al, 2013; Mouralidarane et al, 2013; Pruis et al, 2014; Zhang et al, 2013) in the offspring in most studies. For example, Chen and colleagues report that homeostatic model assessment of insulin resistance (HOMA-IR) was similar among rat offspring with high fat prenatal diet alone (0.46) compared to control prenatal and post-weaning diet (0.35); elevated among those with control prenatal and high fat post-weaning diet (0.62); and dramatically elevated among those with high fat control and post-weaning diet combined (1.15; p for interaction>0.05) (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%